Village Economic Progress: Exploring the Impact of the Smart Village Program in Lampung Province 2020-2024 - Endriyono; Gunarto, Toto; Yuliawan, Dedi (International Journal of Economics, Business, and Entrepreneurship, 2024)
The aim of this research is to analyze the feasibility of the Smart Village program as the government's flagship program in strengthening the village economy, as well as assessing the program's achievements based on the criteria set by the Ministry of Villages PDTT and the Lampung Provincial Government. It is hoped that this research can contribute to the development of more effective and sustainable village development policies in Indonesia.c Smart villages are significantly influenced by a smart economy and a smart society, with both having a strong positive impact. This means that improvements in the economy and the quality of smart communities will increase the smart village index. In addition, smart mobility also has a positive effect but with a lower level of significance. However, the variables smart government and smart life do not have a significant influence on smart villages. Thus, the main focus for improving smart villages should be directed at improving the economy, community quality and mobility.